The Effect of Carbamide Peroxide on Surface Enamel Structural Changes and Streptococcus mutans Attachment - Kezia Nugrahini Anggakusuma; Deviyanti Pratiwi; Armelia Sari Widyarman (Faculty of Dentistry, Universitas Trisakti, 2020)
Background: Home bleaching with carbamide peroxide is commonly used due to its high success rate and minimum side effects. Although home bleaching is safe, it causes structural changes in surface enamel, thereby facilitating Streptococcus mutans attachment on the enamel surface. Objectives: This study aimed to determine the effect of carbamide peroxide concentration on surface enamel structural changes and S. mutans attachment. Methods: Healthy, caries‑free, and calculus‑free upper first premolars were divided into 10%, 15%, and 35% carbamide peroxide concentration groups, with five samples in each group. Structural changes in the surface enamel of the teeth before and after the bleaching procedure were assessed subjectively based on observations using a stereomicroscope at × 40. The samples were inoculated in S. mutans culture and ncubated for 24 h (37°C) in anaerobic conditions. The samples were then washed with phosphate‑buffered saline, and bacterial attachment was released by vortexing for 1 min. Bacterial attachment was assessed using a turbidimetry test and total plate count test. Result: Structural changes in enamel were observed in the samples exposed to carbamide peroxide 35%. The results of an analysis of variance test revealed a significant difference (P < 0.05) in the bacterial attachment test. The samples exposed to carbamide peroxide 35% exhibited the highest amount of bacterial attachment (3 × 106 CFU/mL, optical density: 0.06). Conclusion: The concentration of carbamide peroxide plays a role in structural changes in enamel and S. mutans attachment.